Pertanggungjawaban Korporasi dalam Transfer Teknologi Dual-Use yang Berkontribusi pada Proliferasi Senjata Pemusnah Massal - Kana Kurnia (Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK), 2025)
The role of transnational corporations in the transfer of dual-use technology increases the risk of the proliferation of Weapons of Mass Destruction (WMD) globally. This research aims to analyze international legal arrangements and formulate an ideal corporate liability model to be applied in Indonesia. This study uses a normative juridical method with a comparative legal approach to practice in the United States (US) and the European Union. The results of the study show that regulations in Indonesia are still sectoral and inadequate in meeting the standards of UNSCR 1540 (2004). It was concluded that Indonesia needs to establish a hybrid regulatory ecosystem through the new Strategic Trade Management (STM) Law. This ideal model requires the implementation of the Internal Compliance Programme (ICP) and Know Your End-User (KYE) due diligence as a precaution, as well as integrating rapid administrative sanctions and severe penalties as enforcement mechanisms.